Pioneers of electric mobility: Lessons about transport decarbonisation from two bay areas. (1st January 2022) - Tsoi, Ka Ho; Loo, Becky P.Y.; Tal, Gil; Sperling, Daniel
Abstract: Electric mobility has the potential to spearhead transport decarbonisation. While there is a vast literature on the potential benefits of electric vehicles (EVs) towards sustainability and national policies of EV adoption, regional and local polices are often overlooked. Hence, this paper aims to capture lessons learned from two bay areas, namely the Guangdong-Hong Kong-Macau Greater Bay Area (GBA) in China and the San Francisco Bay Area (SFBA) in the United States. These two regions are pioneers in electric mobility within the two largest economies of the world. An integrative methodology of transport decarbonisation and backcasting analysis are applied to analyse the progress achieved so far (2000–2018) and to project future carbon reduction potentials (2019–2050). Regional and local transport CO2 emissions are estimated by a distance-based approach. The results illustrate that electric mobility has led to carbon reductions of 1.73 Mt CO2 and 0.25 Mt CO2 in 2018 in GBA and SFBA respectively, contributing to a relative decoupling status in both regions ( e  = 0.85 & e  = 0.14). Intra-regional variability in decoupling status is observed, with stronger spatial variations in GBA. The backcasting analysis suggests that the EV share needs to reach almost 100% before 2035 so that the 450 Delayed Action vision can be achieved. This requires a proactive policy package of cleaner electricity with emissions performance standards, EV sales mandates, expanded public charging infrastructure, and a range of measures to incentivize EV market uptakes. Major driving forces of decoupling, including vehicle kilometre travelled, public transport share, and regional/local EV policies, are also identified and discussed. Highlights: Progress and state of electric mobility in the Great Bay and San Francisco Bay areas were estimated. Spatial and temporal changes in road transport carbon emissions of the two bay areas were examined. Backcasting analysis to achieve the 450 Delayed Action vision is conducted with three policy packages. Comprehensive regional-local policies are essential in accelerating electric vehicle market uptake. High electric vehicle market uptake and clean electricity grid are duly critical to transport decarbonisation.